Association between nasogastric tube feeding and discharge outcomes in patients aged 80 and older with aspiration pneumonia: A propensity score‐matched retrospective cohort study - Misa Kitamura; Toshinori Nishizawa; Atsushi Yanai; Masako Taguchi; Noriko Matsumoto; Kuniyoshi Hayashi; Hiroko Arioka (Journal of General and Family Medicine)
Abstract Background This study investigated the association between nasogastric tube feeding (NGF) and discharge rate to previous residences with oral intake in patients aged 80+ with aspiration pneumonia. Methods A retrospective cohort study included 256 hospitalized patients with aspiration pneumonia from 2012 to 2022, which could not start oral intake within 48 h due to dysphagia. Using 1:2 matched‐pair analysis, the association of interest was examined using logistic regression analysis. Results NGF was associated with a lower discharge rate (odds ratio: 0.15; 95% CI: 0.05–0.46). Conclusion Patients with NGF had a lower discharge rate to previous residences with oral intake.